Developing Interactive Multimedia for Teaching Reading Comprehension on Narrative Texts Based on South Sumatera Local Culture - Heru Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The objectives of this study were to find out the validity, practicality, and effect of interactive multimedia for teaching reading comprehension on narrative texts based on South Sumatera local culture. This reasearch was development research by adapting the ADDIE model consisting of analysis, design, development, implementation, and evaluation. The subjects of this study were 25 fourth-semester students of Tridinanti University. This study found that The interactive multimedia for teaching narrative texts based on South Sumatera local culture were valid in terms of its contents, construct and after evaluated by three experts review. The total average score of the validity was 3.53. It was indicated at high validity level. This media was practical after evaluated in one-to-one evaluation with an average score (3.63) and small group evaluation with an average score (3.78). It was indicated at high practical Level. Moreover, it also had a potential effect after tried out in field test. It was determined by the result of students’ achievement in reading comprehension test since 72 % of the students pass.